Identification of Interacting Proteins of Transcription Factor DpAP2 Related to Carotenoid Biosynthesis From Marine Microalga Dunaliella parva - Shang, Changhua; Pang, Bingbing; Zhang, Jin; Yu, Lihong; Gan, Shanling; Li, Yujia; Wu, Haifeng (Frontiers in Marine Science, 2022)
Carotenoids are widely distributed and structurally diverse, which have significant roles in photosynthesis of plants. As precursor of vitamin A, carotenoids are also antioxidants reducing various chronic diseases, which are beneficial for human health. Currently, the existing studies concerned the biological roles of APETALA2 (AP2)/Ethylene Responsive Factor (ERF) genes originated from higher plants. The AP2 superfamily of transcriptional regulator was identified in higher plants, which was related to growth, development, carotenoid metabolism and responses to various stress. However, the regulatory mechanisms of AP2 modulating carotenoid metabolism have not been reported in microalgae, which remain to be elucidated. Dunaliella parva, AP2 (i. e. DpAP2), an important transcription factor, promotes carotenoid accumulation by binding to the promoter of target gene. Here we identified an important AP2/ERF transcription factor Dunaliella parva (D. parva) AP2 (i. e. DpAP2) which could promote carotenoid accumulation by binding to the promoter of target gene. To demonstrate the function of DpAP2, the interacting proteins were identified by yeast two-hybrid system. The results showed that DpAP2 could interact with three proteins with different activities (DNA-binding transcription factor activity, protein kinase activity and alpha-D-phosphohexomutase activity), these proteins may be associated with multiple biological processes. We proposed that DpAP2 participated in a regulatory network controlling carotenoid biosynthesis. This paper laid a good foundation for a deep understanding of the regulatory mechanisms of DpAP2 and genetic engineering breeding in D. parva.